Post-COVID-19 Behavioral Determinants of Unmanned Aircraft Adoption in Bangkok’s Urban Mobility - Charoensook, Chartchai; Pholsook, Thitinan; Jomnonkwao, Sajjakaj; Se, Chamroeun; Ratanavaraha, Vatanavongs (Asia Social Issues, 2025)
In recent years, public transportation has evolved to offer faster and more efficient options. One emerging concept is using unmanned aircraft for vertical take-off and landing (VTOL-UAs) to enhance urban mobility. Although not yet implemented in Thailand or abroad, this study examines factors influencing the decision to use unmanned aircraft for public transportation in the Bangkok Metropolitan Region. Guided by the Unified Theory of Acceptance and Use of Technology (UTAUT), the researchers collected data from 1,200 participants through face-to-face questionnaires and analyzed the responses using Structural Equation Modeling (SEM). The results indicate a strong willingness among participants to use unmanned aircraft and share flights if such options become available. Gender differences significantly influenced decision-making, while age showed no overall impact, though respondents under 30 expressed the most positive attitudes. SEM analysis identified achievement, social influence, convenience, and performance as key factors, with weights of 0.325, 0.217, 0.193, and 0.143. These findings provide valuable insights for developing unmanned aircraft as a mass transit option, with implications for the public and private sectors. Educational institutions may also use these results to guide curriculum development in transportation and unmanned aircraft systems.